Bacteriostatic activity and cytotoxicity of bacterial cellulose-chitosan film loaded with in-situ synthesized silver nanoparticles. (1st April 2022) - Zhao, Hang; Zhang, Liang; Zheng, Sen; Chai, Shouning; Wei, Jinliu; Zhong, Lvling; He, Yingying; Xue, Juanqin
Abstract: Bacterial infections on open wounds have always been a threat to human health. Herein, we prepared a silver (Ag)-polydopamine (PDA)/bacterial cellulose (BC)-chitosan (CTS) film using biological self-generation and in situ reduction. CTS was added to culture medium to allow BC to intertwine with CTS during film formation. Silver nitrate was reduced in situ to Ag nanoparticles under ultraviolet irradiation, and the nanoparticles were well dispersed in the BC-CTS film with the help of PDA, which worked synergistically with the CTS. The Ag-PDA/BC-CTS film was enriched in functional groups, and it had good tensile and swelling properties. The inhibition film demonstrated broad-spectrum inhibition of Gram-positive and Gram-negative bacteria, and this inhibition was maintained at more than 80% after 48 h of continuous use. The good biocompatibility of the film was verified using NIH3T3 fibroblasts. The results suggested that the Ag-PDA/BC-CTS film inhibited the growth of harmful bacteria while having little effect on healthy cells.